A Structural Study of the Cytoplasmic Chaperone Effect of 14-3-3 Proteins on Ataxin-1. Issue 19 (17th September 2021) - Leysen, Seppe; Burnley, Rebecca Jane; Rodriguez, Elizabeth; Milroy, Lech-Gustav; Soini, Lorenzo; Adamski, Carolyn J.; Nitschke, Larissa; Davis, Rachel; Obsil, Tomas; Brunsveld, Lucas; Crabbe, Tom; Zoghbi, Huda Yahya; et al.
Graphical abstract: Highlights: 14-3-3 was postulated to prevent cytoplasmic aggregation of Ataxin-1. Experimental support for an anti-aggregation effect of 14-3-3 on Ataxin-1 is provided. Structural studies suggest 14-3-3 reduces Ataxin-1 dimerisation and further self-association. Modulation of the 14-3-3/Ataxin-1 interaction could provide a treatment for SCA1. Abstract: Expansion of the polyglutamine tract in the N terminus of Ataxin-1 is the main cause of the neurodegenerative disease, spinocerebellar ataxia type 1 (SCA1). However, the C-terminal part of the protein – including its AXH domain and a phosphorylation on residue serine 776 – also plays a crucial role in disease development. This phosphorylation event is known to be crucial for the interaction of Ataxin-1 with the 14-3-3 adaptor proteins and has been shown to indirectly contribute to Ataxin-1 stability. Here we show that 14-3-3 also has a direct anti-aggregation or "chaperone" effect on Ataxin-1. Furthermore, we provide structural and biophysical information revealing how phosphorylated S776 in the intrinsically disordered C terminus of Ataxin-1 mediates the cytoplasmic interaction with 14-3-3 proteins. Based on these findings, we propose that 14-3-3 exerts the observed chaperone effect by interfering with Ataxin-1 dimerization through its AXH domain, reducing further self-association. The chaperone effect is particularly important in the context of SCA1, as it was previously shown that a soluble form of mutant Ataxin-1 is the major driver of pathology.